2020
DOI: 10.1155/2020/9246758
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Safety and Efficacy of Nivolumab in Advanced Squamous and Nonsquamous Non-Small-Cell Lung Cancer: A Retrospective Cohort Study in Croatia, Hungary, and Malta

Abstract: Background. There is a lack of real-world data on the safety and efficacy of nivolumab in patients with previously treated advanced non-small-cell lung cancer (NSCLC) especially in South East Europe, a region with particularly high incidence and an unfavorable mortality-to-incidence ratio for lung cancer. Objectives. To evaluate the real-world safety and efficacy of nivolumab in patients with previously treated advanced squamous and nonsquamous NSCLC in South East Europe. Methods. This is a multicenter, retros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…16 A larger European study recruiting nivolumab-treated patients in Hungary, Malta, and Croatia found that 10 out of 239 (4.2%) patients developed hypothyroidism. 17 A study in Japan found that hypothyroidism developed in 67 out of 200 (33.5%) nivolumab-treated patients. 18 A study carried out in Texas recruited 657 patients treated with an ICI, of whom 43 developed thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A larger European study recruiting nivolumab-treated patients in Hungary, Malta, and Croatia found that 10 out of 239 (4.2%) patients developed hypothyroidism. 17 A study in Japan found that hypothyroidism developed in 67 out of 200 (33.5%) nivolumab-treated patients. 18 A study carried out in Texas recruited 657 patients treated with an ICI, of whom 43 developed thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…25 In a real-world cohort, pneumonitis occurred in 5 of 239 patients (2.1%) treated with nivolumab. 17 The risk factors for ICI-induced pneumonitis are exposure to tobacco smoke and higher lung tumor burden. It is not known if past thoracic radiotherapy or chronic obstructive pulmonary disease increases the risk of pneumonitis.…”
Section: Discussionmentioning
confidence: 99%